(untitled) (Research, Society and Development, 2022)
This paper deals to analyze the concept of additional languages present in the documents that regulate their teaching at a national scope. The methodology is configured as an approach that tends both to bibliographic survey method and document analysis. To carry out this discussion, we count on the contributions of Bakhtin; Saussure); Chomsky; which we make use of for the conception of language; we rely on the discussions supported by those who are committed to the studies of Applied Linguistics: Fabrício; Moita Lopes; Pennycook; We also bring the contribution of Leffa & Irala regarding the conceptualization of additional languages and, finally, we have the contributions of authors who are willing to discuss aspects related to the National Common Curricular Base (BNCC): Macedo; Branco et al; Brasil; Pfeiffer & Grigoletto. The analysis reveals the exclusive character of the BNCC when it comes to the teaching-learning process of additional languages, since, based on the present study, we infer that this document brings some controversies in addition to not aiming to promote a plurilingual education.